موقف الفكر الحداثي من السنة النبوية-محمد شحرور أنموذجا - رحال, فائزة (University of Eloued جامعة الوادي, 2017)
يأتي هذا الموضوع إلى التعريف بالفكر الحداثي عموماً وبمحمد شحرور على وجه الخصوص، من خلال ثلاثة فصول حاولت فيها تجميع لبنات الموضوع، فالفصل التمهيدي احتوى على التعريف اللغوي والاصطلاحي للحداثة، بعدها عرجت على كشف تاريخ نشأة هذا الفكر مع بيان خصائصه وأهدافه وآثاره على الواقع الإسلامي ثم سلكت منحى آخر وهو تعريف السنة النبوية عند بعض الحداثيين، وفي المبحث الثاني ذكرت بعض الاتجاهات التي لها علاقة وطيدة بالحداثة وهي العلمانية والاستشراق والقرآنيون، واكتفيت بتعريف هذه الاتجاهات مع ذكر خصائصها وربط العلاقة بينها وبين الحداثة. أما الفصل الأول فهو خاص بالتعريف بمحمد شحرور وبأفكاره ومؤلفاته والمبحث الثاني اختصرته على كتابيه الأول "الكتاب والقرآن قراءة معاصرة" والثاني كتاب "تجفيف منابع الإرهاب"، وختمت الدراسة بالفصل الثاني والأخير خُصص لدراسة كتاب "السنة الرسولية والسنة النبوية"، فكان المبحث الأول حول نقده للإمام الشافعي وتأسيسه لحجية السنة بعده تناولت تعريف شحرور للسنة مع التفريق بين الرسول والنبي ونقده لحجية الصحابة وعلوم الحديث، هذا وكان المبحث الأخير عبارة عن بعض النماذج لأحاديث صحيحة ثابتة انتقدها شحرور وشكك في ثبوتها وعمل على إبطالها ولزيادة توضيح فإن كتاب شحرور زاخر بالأمثلة. وبعد كل ما ذكر سابقا توصلت إلى: 1-أن عموم شبهات الحداثيين من العرب المسلمين هي استنساخ لشبهات أعداء السنة القدامى من المعتزلة والزنادقة. 2-انحياد الحداثيين للموضوعية في كلامهم عن الحديث النبوي، وهذا ما يظهر جليا في مؤلفاتهم. The aim of this topics is to introduce the general thought of modernity and Mohammed shahrour to in particular througlr three chapters in which I tried assemble the blochs of the topic the introductory chapter contained the linguistic and terminologicald efinition of alhadath. Then I stopped by revealing the history of the origis of thisthought indicating it characteristics obgectives and effect on the Islamic reality and then I took another direction the definition of the prophetic year at some of the two modernity and in the second Its has a close relationship with modernity secularism Aschorh and Quranic, and has merehy defined these trends with their characteristics and the relationship between them and modernity, the first chapter is to publicize Mohammed shahrour his writing and the second study I shortened him to his book, the authors, the koram reading contemporary and the second book drying up the sources of terrosim and conclude with the second and final chapter was devoted and final chapter was devoted to the study of the holy year and the Sunnah the first one his criticism of the Imam and the establishement of the: 1. Hajj of the year after which I dealt with the distinction between the prophet and the prophets and his Qriticism of the hajj and the modern science of this the last post is some escample of valid static conversation criticized by shahrour and after all Ifound that the general liheness of the modernity muslim Arabs are a clone of the suspicions of the ancient Sunni enemies of the MATZLH Walznadika the modernity of objectivity in their talk about the prophetic. 2. Hadith and this maizher is evident in their writings.
مذكرة ماستر تخصص علوم الحديث
Keywords: الحداثة- محمد شحرور - السنة; Mohammed shahrour- alhadatha- Sunnah.